+0  
 
+1
134
1
avatar

what is 6(v-1)-4=-3(-2+8)-8v

Guest Jun 8, 2017
Sort: 

1+0 Answers

 #1
avatar+64 
+1

Simplifying -6(v + 1) + 8 = 2(v + -3)

 

Reorder the terms: -6(1 + v) + 8 = 2(v + -3) (1 * -6 + v * -6) + 8 = 2(v + -3) (-6 + -6v) + 8 = 2(v + -3)

 

Reorder the terms: -6 + 8 + -6v = 2(v + -3)

 

Combine like terms: -6 + 8 = 2 2 + -6v = 2(v + -3)

 

Reorder the terms: 2 + -6v = 2(-3 + v) 2 + -6v = (-3 * 2 + v * 2) 2 + -6v = (-6 + 2v)

 

Solving 2 + -6v = -6 + 2v Solving for variable 'v'.

 

Move all terms containing v to the left, all other terms to the right.

 

Add '-2v' to each side of the equation. 2 + -6v + -2v = -6 + 2v + -2v

 

Combine like terms: -6v + -2v = -8v 2 + -8v = -6 + 2v + -2v

 

Combine like terms: 2v + -2v = 0 2 + -8v = -6 + 0 2 + -8v = -6

 

Add '-2' to each side of the equation. 2 + -2 + -8v = -6 + -2

 

Combine like terms: 2 + -2 = 0 0 + -8v = -6 + -2 -8v = -6 + -2

 

Combine like terms: -6 + -2 = -8 -8v = -8

 

Divide each side by '-8'. v = 1

 

Simplifying v = 1

 

smiley

cheifraidhunter  Jun 8, 2017

8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details